The theory of money value and monetary evolution for Simmel and Mises - Zelmanovitz, Leonidas Zelmanovitz (REVISTA PROCESOS DE MERCADO, 2010)
The essay starts positioning Simmel as a bridge between the money value theories of Menger and Mises, and claiming that his contribution is important in its own right; notably, his idea that money evolves towards more abstract forms as society becomes more complex. It states that this trend exists and that its course has not yet been completed. After that, the theories of money value of Menger, Mises and Simmel are succinctly described, with emphasis on the contributions to Mises’ theory of money value that can be traced back to Simmel. About Simmel’s theory of money value, it is argued that Simmel went one step further than Menger in stating that value is not only subjective but also inter-subjective; such a move is understood as a necessary step in his argument that there is a trend towards more abstract forms of money as society evolves. Key words: Value Theory, Austrian School, Definition of Money, Payment Systems. JEL Classification: B10, B13, E40, E42. Resumen: Este trabajo empieza planteando que Simmel es un puente de unión entre las teorías de valor del dinero de Menger y Mises, y que su contribución es importante por sí misma. En este sentido, destaca su idea de que el dinero se vuelve más abstracto con el desarrollo de la sociedad. Posteriormente, describe sucintamente las teorías del valor del dinero de Menger, Mises y Simmel, poniendo énfasis en las contribuciones de Simmel acerca de la teoría de valor del dinero de Mises. Respecto a la teoría del valor del dinero de Simmel, se plantea que supuso un paso adelante en relación a Menger, al afirmar que el valor del dinero no es solamente subjetivo sino ínter-subjetivo. Esta afirmación es un paso necesario en su argumento de que existe una tendencia hacia formas más abstractas de dinero conforme la sociedad se torna más compleja. Palabras clave: Teoría del valor, Escuela Austriaca, definición de dinero, sistema de pagos. Clasificación JEL: B10, B13, E40, E42.